PTU-065 Four-Way Comparison of Elisa Methods Available for the Measurement of Infliximab and Anti-Infliximab Antibody in IBD Patients. (17th August 2016) - Unsworth, N; Samaan, MA; Warner, B; Arkir, Z; Irving, PM
Abstract : Introduction: Commercial assays are now widely available and in routine use for the therapeutic drug monitoring of Infliximab (IFX) and anti-Infliximab antibody (ADAb). Although results generated using these assays are used to guide clinical decision making, there is no standardisation and data assessing the comparability between these assays is lacking. Methods: A prospective evaluation of IFX drug levels and ADAb was performed using our standard ELISA assay; LISA TRACKER (Theradiag) and also Promonitor (Proteomika), IDKmonitor (Immundiagnostik) and RIDASCREEN IFX (R-Biopharm AG / KU Leuven) ELISA assays. 105 samples from 102 IBD patients were analysed for IFX, free ADAb (LT/PRO) and total ADAb (ID) automated on eRobot and Grifols Triturus analysers. LT, PRO and RS kits were provided at no cost.Method comparisons were performed using difference plots and Passing Bablok analysis. Results: A summary of IFX drug level comparison data is shown in the image below. The distribution of bias between methods was variable (-6.7% to +87.8%) with PRO and ID showing scattered, bimodal distributions of %bias. A consistent, proportional relationship was observed between LT and RS results. Free ADAb were detected in 4/105 (3.8%) samples using LT and 3/105 using PRO. All patients with detectable free ADAb had undetectable IFX drug levels. Conversely, total ADAb were detected in 23/105 (21.9%) samples but IFX drug levels were sub-therapeutic (<1.0 ug/mL) in only 6/23 (26.1%) of these and therapeutic (>2.0 ug/mL) in the majority of cases (13/23). Conclusion: These results show that there is significant variation in IFX drug levels obtained when using different CE marked ELISA assays and as such, results are not directly comparable. Although the clinical utility of measuring total ADAb is yet to be established, a significant proportion of patients tested will be positive for total ADAb irrespective of therapeutic IFX drug levels. In the absence of assay standardisation and external quality assurance, laboratory providers and clinicians should ensure that assays currently in routine use are fit for purpose. Disclosure of Interest: None Declared